Construction Technologies of Self-compacting Concrete for Lining of Water Conveyance Shield Tunnel - SHI Aijun; WANG Yongjian; YAO Chukang; XIE Xiangming; WU Yulong; CAI Yixin (Renmin Zhujiang)
Some problems exist in the construction of composite lining of water conveyance shield tunnel,such as vertical transportation of self-compacting concrete (SCC) in deep work shafts,long-distance horizontal transportation of SCC in tunnels,and placing and casting of SCC in closed ring structures.In response to them,a transportation method and a placing mode suitable for SCC were chosen.The spacing of casting holes on the lined steel pipe (inner mold) was reasonably determined for SCC through a simulation test.Depending on the characteristics of the composite lining structure and the construction performance of SCC,related calculations and analyses are carried out for reasonable determination of the casting process and quality control measures such as the length of casting section,layer thickness,and placing speed.The determined parameters were applied in the pilot project of Shenzhen main branch of the Water Resources Allocation Project in the Pearl River Delta.We found that no aggregate separation occurred during the transportation of SCC,and the lined steel pipe did not float up or drift sideward during the casting of SCC.The drilling and coring test results showed that the height of the void between SCC and outer lining segment on the vault met the design requirements,and the lining space of closed ring structures was filled after backfilling and grouting.These results indicate that the SCC of composite lining is of good quality.Relevant construction technologies can provide references for the construction of similar projects.